TRANSITIVITY PROCESS OF DONALD TRUMP’S POLITICAL SPEECH - Elisa Silviani Siregar; Zainuddin Zainuddin; Sri Minda Murni (LINGUISTIK TERAPAN, 2019)
The objectives of the research are to identify how Donald Trumps realized his political motivation on his speech. The research picked Donald Trumps last speech campaign 2017. Here, the researcher will focus on identifying the way of political motivations are realized in Donald Trumps speech. The data were taken from Donald Trumps speech  transcript that downloaded from internet and analyzed. Based on the result of data analysis, it is found that the motivation realized in Donald Trumps Speech are realized through 3 themes in his speech. They are Being Unity, American Issues and Citizen involvement.  Keywords: PoliticalSspeech, Donald Trump, Motivation, Transitivity